1978
DOI: 10.1007/bf00442166
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic sarcoma complicating osteogenesis imperfecta tarda

Abstract: We describe the case history of a 13 years old boy who developed osteogenic sarcoma of the left thigh, six years after diagnosis of osteogenesis imperfecta tarda with a positive family history. Only four other patients with this disease combination are reported in the literature. Preoperative treatment with high-dose Methotrexate caused marked tumor regression, as shown at examination of amputation material. The inter-relationships between the two disorders are discussed and the literature is briefly reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1984
1984
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…There have been only nine reported cases in the world literature (Table 1) [2,5,8,9,10,11,18,19], and most authors concluded that osteosarcoma in the setting of OI occurred as a sporadic, rather than a related, event. More important, however, is the fact that osteosarcoma is difficult to diagnose in patients with OI, which was Factors that have been proposed as possible etiological agents in primary bone tumors are radiation, viruses, chemical carcinogens, metal implants, and trauma [17].…”
Section: Discussionmentioning
confidence: 99%
“…There have been only nine reported cases in the world literature (Table 1) [2,5,8,9,10,11,18,19], and most authors concluded that osteosarcoma in the setting of OI occurred as a sporadic, rather than a related, event. More important, however, is the fact that osteosarcoma is difficult to diagnose in patients with OI, which was Factors that have been proposed as possible etiological agents in primary bone tumors are radiation, viruses, chemical carcinogens, metal implants, and trauma [17].…”
Section: Discussionmentioning
confidence: 99%
“…Three cases listed in Tables 1 and 2 were informed by Prof. Spranger and these consisted of the cases reported by Lasson et al (1978) and Rutkowski et al (1979), and one case from Dr. Dahlin. From the orthopaedic clinics in Japan, no case was cited.…”
Section: ) Osteosarcoma Arising In Osteogenesis Imperfecta Tardamentioning
confidence: 99%
“…Since then, several cases have been reported in the literature (Roschlau, 1962;Klenerman et al, 1967;Lasson et al, 1978;Rutkowski et al, 1979;Reid and Hubbard, 1979). Rutkowski reported a 15-year-old boy and stated that osteosarcoma was extremely rare in association with osteogenesis imperfecta tarda, and that only 8 cases have been reported in the literature.…”
Section: ) Osteosarcoma Arising In Osteogenesis Imperfecta Tardamentioning
confidence: 99%
See 1 more Smart Citation
“…At this moment, however, little is known about the condition. The imaging and histological similarity of this hyperplastic callus formation to an osteogenic sarcoma raises great concern among orthopedic surgeons [2][3][4]7,9,10,12,14,[16][17][18][19][20][21][22][23][24][25]. The imaging and histological similarity of this hyperplastic callus formation to an osteogenic sarcoma raises great concern among orthopedic surgeons [2][3][4]7,9,10,12,14,[16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%